Promoting information-resource sharing within the enterprise: A perspective of blockchain consensus perception - Gang Li; Chih-Cheng Fang (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The prevalence of information technology (IT) and information systems (IS) provides opportunities for enterprises to sustain open innovation. However, information silos that appeared with IS use have made IS inconvenient and thus impeded enterprises' open innovation. The present study, therefore, aims to resolve this issue by helping understand how to encourage information-resource sharing within the enterprise. We first proposed a new concept-consensus perception-based on the blockchain characteristics and advantages derived from prior studies, and then developed a conceptual model based on the consensus perception and principal-agent theory. Second, we used this conceptual model to investigate whether blockchain technology (BT) can be used to promote information-resource sharing. The results showed that information security concern, perceived rewards, and openness have direct influences on information-resource sharing intention and that trust has indirect effects. The findings provide useful theoretical and practical contributions to sustain enterprises' open innovation by adopting BT to solve the information-resource sharing issues.
Keywords: 650; blockchain; information-resource sharing; consensus perception; trust; openness; informationsecurity concern; perceived rewards; open innovation